1995
DOI: 10.1037/0022-3514.69.3.397
|View full text |Cite
|
Sign up to set email alerts
|

The dissection of selection in person perception: Inhibitory processes in social stereotyping.

Abstract: Although people simultaneously belong to multiple social categories, any one of these competing representations can dominate the categorization process. It is surprising therefore to learn that only a few studies have considered the question of how people are categorized when multiple categorizations are available. In addition, relatively little is known about the cognitive mechanisms through which these categorization effects are realized. In the reported research, we attempted to extend recent ideas from wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
332
4
7

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 364 publications
(367 citation statements)
references
References 56 publications
24
332
4
7
Order By: Relevance
“…Our affective reaction toward this stimulus could reflect our positive attitude toward the person we are seeing, the negative attitude toward the facial expression that the person is displaying, or both. The present results suggest that affective reactions will be mainly guided by the attitude toward the feature that is most salient or relevant to us within the context where we encounter the attitude object (see also Macrae, Bodenhausen, & Milne, 1995). The data showed that the name of a British person automatically induced a tendency to give a response that was associated with positive valence, regardless of whether the person was a popular comedian or a convicted mass murderer.…”
Section: Discussionmentioning
confidence: 75%
“…Our affective reaction toward this stimulus could reflect our positive attitude toward the person we are seeing, the negative attitude toward the facial expression that the person is displaying, or both. The present results suggest that affective reactions will be mainly guided by the attitude toward the feature that is most salient or relevant to us within the context where we encounter the attitude object (see also Macrae, Bodenhausen, & Milne, 1995). The data showed that the name of a British person automatically induced a tendency to give a response that was associated with positive valence, regardless of whether the person was a popular comedian or a convicted mass murderer.…”
Section: Discussionmentioning
confidence: 75%
“…Conditional automaticity effects occur when an automatic process is triggered only in the presence of certain conditions, such as the presence of a specific goal (Bargh 1989;Blair 2002). For example, although exposure to members of minority groups frequently triggers automatic stereotypes of those groups, this automatic stereotype activation depends upon the presence of perceivers' goals, contextual factors, and features of the group members (Blair 2002;Dasgupta and Greenwald 2001;Macrae, Bodenhausen, and Milne 1995;Mitchell, Nosek, and Banaji 2003;Sinclair and Kunda 1999;Spencer et al 1998). Similarly, we suggest that consumers' purchase intentions following fast disclaimers for trust-unknown, not-trusted, and trusted brands derive from a conditionally automatic process.…”
Section: Discussionmentioning
confidence: 99%
“…Faces can be assigned to multiple, partially overlapping, social categories that may competes and inhibit each other (Macrae et al 1995;Higgins 1996). Specifically, a face can simultaneously be categorized as a human, a man, a famous person, an ethnic minority member, and so on, and the activation of a particular category can be influenced by task context.…”
Section: Discussionmentioning
confidence: 99%